Canadian Air Law for Pilots - Fafard, Alexis J. D. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
Canada is a global aviation powerhouse. Thanks to the British Commonwealth Air Training Plan during World War II, as well as its internationally-recognized reputation enabling an important and meaningful bridge among the nations of the world after the war, Canada - called the Aerodrome of Democracy by President Franklin D. Roosevelt - was chosen as the host of the headquarters of the United Nations' International Civil Aviation Organization (ICAO) and influential International Air Transport Association (IATA), and has become the third-largest aerospace hub in the world. Today, thousands of Canadian aviation professionals specializing in engineering, management, finance, sales, flight operations, academics, flight training, tax, and law staff the ICAO, IATA, governmental agencies, airline companies, law and aircraft leasing firms, universities, and gigantic aerospace corporations. This Canadian expertise also resonates in today's global training pipeline of highly skilled professionals operating winged-tubes loaded with thousands of gallons of kerosene fuelling complex and powerful engine systems in the lower levels of the stratosphere to carry passengers and/or cargo across intercontinental airways. Canadian Air Law for Pilots is entirely dedicated to pilots; its purpose is twofold: (1) to highlight the landmark Canadian legislative framework relative to aviation law, and provide an extensive review of federal decision-makers affecting pilots' privileges, rights, and interests by reporting on their purposes, procedural rules, as well as key case law within administrative and penal law; and (2) to outline Canada's air law for local and international applicants and trainees interested in obtaining pilot permits, licences or ratings (aeroplanes) issued by Transport Canada. This textbook is divided into four parts: Part I: Administrative Law Part II: Penal Law Part III: Aircraft in Canada Part IV: Air Law.
Introduction -- Part I. Administrative Law -- Chapter 1. Principal Statutes Pertinent to Air Law and Pilots -- Chapter 2. Canadian Civil Aviation Regulatory Authorities and Agencies -- Chapter 3. Administrative Tribunals and Courts of Law -- Chapter 4. Pilots and Canadian Decision-Makers under Air Law -- Part II. Air Law -- Chapter 5. General Provisions and Aircraft Registration and Operation -- Chapter 6. Personal Licensing and Training -- Chapter 7. Aerodromes and Airports -- Chapter 8. Canadian Airspace -- Chapter 9. Flight Operations in Canada -- Chapter 10. Visual Flight Rules -- Chapter 11. Instrument Flight Rules -- Chapter 12. Radiocommunications -- Chapter 13. Airworthiness - Cargo Compartment Classification -- Chapter 14. Operational and Emergency Equipment Requirements -- Chapter 15. Flight Preparation, Flight Plans and Flight Itineraries -- Chapter 16. Pre-Flight and Fuel Requirements -- Chapter 17. Special Flight Operations -- Chapter 18. Private Operator Passenger Transportation -- Chapter 19. Aircraft Requirements -- Chapter 20. Commercial Air Services -- Part III. Penal Law -- Chapter 21. General -- Chapter 22. Offences -- Part IV. Aircraft In Canada -- Chapter 23. General -- Chapter 24. Miscellaneous.
Keywords: Law of the sea; International law; Aeronautics-Law and legislation; Social legislation; Administrative law; International criminal law; Law of the Sea, Air and Outer Space; Public International Law; Sources and Subjects of International Law, International Organizations; Labour Law/Social Law; Administrative Law; International Criminal Law